REGENERASI DENDRIT SEL GANGLION RETINA: PERAN INSULIN UNTUK MENGEMBALIKAN PENGLIHATAN PADA GLAUKOMA - Nurul Azizah; Sisca Sisca; Rasiha Rasiha (Al-Iqra Medical Journal : Jurnal Berkala Ilmiah Kedokteran, 2018)
Glaukoma is a leading cause of irreversible blindness worldwide. This disease is associated with characteristic damage to the optic nerve and permanent retinal ganglion cell (RGC) degeneration. A crucial step towards circuit repair in glaucoma is to promote damaged RGCs to regenerate not only axons, but also dendrites to successfully reconnect with their synaptic partners. The latest research showed that insulin signalling has the capacity to regenerate dendrites dan injured synapses, therefore the use of insulin raises a new paradigm as a new pro-regenerative therapeutic target for the disease of glaucoma. This literature review is made using literature searching of valid journals with inclusion and exclusion criteria. On the experiment of insulin’s effectivity, it is valued using 4 indicators; promote dendrite regeneration, restore synaptic density, rescue retinal function, robust neuronal survival. Based on in vivo experiment, insulin endowed with the ability to effectively restore dendritic morphology thus enhancing the function and survival of RGC through mTORC1 (mammalian target of rapamycin complex 1) and mTORC2 (mammalian target of rapamycin complex 2) signalling, this supports that that it can be promising therapeutic targets to counter progressive RGC neurodegeneration and vision loss in glaucoma.